Metamodel analysis on multi-echelon supply chain simulation experiments. (7th July 2010) - Song, Laigang; Li, Xueping; Garcia-Diaz, Alberto
Metamodels are abstractions of a simulation model to reveal the system's input-output relationship through simple mathematical expression. It provides an analytical way to study the behaviour of complex systems. A multi-echelon supply chain is one of such systems, which is usually extremely difficult, if not impossible, to obtain closed-form analytical solutions due to the intrinsic complexity of the inventory system and its underlying uncertainty. In this paper, we apply the methodology of simulation metamodel to a multi-echelon supply chain problem and conduct statistical analysis of the parameters. The metamodel is validated using training experiment conditions.